Batasan Kewajiban Istri Terhadap Pengabaian Tanggung Jawab Suami Perspektif Hukum Fikih - Kemal Lutfi; Deni Irawan; Muhammad Fahmi Mansoor (Yayasan Cendekia Gagayunan Indonesia, 2025)
The household is the smallest social unit formed through a legitimate marital bond according to Islamic teachings. In the Islamic perspective, husbands and wives have balanced rights and responsibilities; the husband serves as the leader and protector of the family, while the wife manages domestic affairs and serves her husband in accordance with sharia provisions. When the husband neglects his responsibilities, the boundaries of the wife's obligations become crucial to maintaining balance and justice within the household, in line with the principles of Islamic jurisprudence (fiqh), which emphasize the harmony of roles and responsibilities to achieve a harmonious family. This study discusses the protection of the wife’s rights in situations where the husband neglects his duties, based on a fiqh perspective, using a qualitative approach with descriptive-analytical methods. It examines the husband’s obligations in Islamic law and the consequences of their improper fulfillment. The analysis also explores the limitations of the wife’s obligations in responding to such conditions in accordance with Islamic legal provisions. The findings indicate that the wife has the right to demand the fulfillment of financial support and legal protection if the husband fails in his responsibilities. Islamic jurisprudence provides a legal basis for the wife to defend her rights through divorce proceedings or legal claims in the religious court. Thus, this study emphasizes the importance of a sound understanding of fiqh in resolving domestic problems related to the rights and obligations of both husband and wife.